IMPROVING THE QUALITY OF LIFE OF PATIENTS WITH CHRONIC GASTRITIS - Maxarram Raxmatovna Saidusmanova (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Helicobacter inhabits the gastric mucosa, causing inflammation and damage. The source of infection is an infected person. It is believed that about 80% of cases of HG are associated with Helicobacter pylori. Chronic gastritis is an inflammatory disease caused by gastric complications caused by infections (most often Helicobacter pylori), autoimmune processes, long-term use of certain medications, as well as bad habits and poor nutrition. The most common cause is damage to the gastric mucosa by the bacterium Helicobacter pylori.